2004
DOI: 10.1111/j.1572-0241.2004.40478.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Somatic Complaints and Health-Care Utilization in Children: Effects of Parent IBS Status and Parent Response to Gastrointestinal Symptoms

Abstract: (i) Frequent GI complaints in children whose mothers have irritable bowel are not explained by the mother's biased perceptions; (ii) children of mothers with irritable bowel have more non-GI as well as GI symptoms, disability days, and clinical visits; (iii) and parent IBS status and solicitous responses to illness have independent effects on the child's symptom complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
154
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 195 publications
(174 citation statements)
references
References 27 publications
14
154
2
4
Order By: Relevance
“…Mothers who participated in the original study by Levy and colleagues 4 completed a research protocol that included the parent report version of the ARCS as a paper questionnaire, and their children completed a child report version of this questionnaire. These protocols were completed in their homes or at their HMO clinic, according to the family's preference.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mothers who participated in the original study by Levy and colleagues 4 completed a research protocol that included the parent report version of the ARCS as a paper questionnaire, and their children completed a child report version of this questionnaire. These protocols were completed in their homes or at their HMO clinic, according to the family's preference.…”
Section: Methodsmentioning
confidence: 99%
“…4 The sample for the larger study (n = 449) included families with children between the ages of 8 and 15 years and in which no family member had a diagnosis of ulcerative colitis or Crohn disease. Approximately half of the mothers who were enrolled in the primary study had received a diagnosis of irritable bowel syndrome at a health care visit to the HMO, Group Health Cooperative of Puget Sound.…”
Section: Methods Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been reported that children of mothers with IBS have more somatic as well as GI symptoms, disability days and clinical visits. 6 The recent genetic studies on the serotonin transporter (SERT) gene-linked polymorphic region (5-HTTLPR) revealed that IBS is not equivalent to SERT dysfunction but SERT dysfunction may contribute to behavioural and functional gut disorders. 7 In the further research on epidemiological studies for IBS, such genetic and environmental (e.g.…”
mentioning
confidence: 99%